2020
DOI: 10.3847/1538-4357/abb677
|View full text |Cite
|
Sign up to set email alerts
|

SOFIA/FIFI-LS Full-disk [C ii] Mapping and CO-dark Molecular Gas across the Nearby Spiral Galaxy NGC 6946

Abstract: We present SOFIA/FIFI-LS observations of the [C II] 158 μm cooling line across the nearby spiral galaxy NGC 6946. We combine these with UV, IR, CO, and H I data to compare [C II] emission to dust properties, star formation rate (SFR), H 2 , and H I at 560 pc scales via stacking by environment (spiral arms, interarm, and center), radial profiles, and individual, beam-sized measurements. We attribute 73% of the [C II] luminosity to arms, and 19% and 8% to the center and interarm region, respectively. [C II]/TIR,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 89 publications
(154 reference statements)
1
30
0
Order By: Relevance
“…We can compare FIFI+LS performance improvement to recent observations of FIFI-LS. Indeed, a comparable observation has already been completed with FIFI-LS for NGC6946 in [CII] by Bigiel et al 10 This map was completed in 9.5 h total, providing a signal-to-noise ratio of 4 for a line flux of 1.3 × 10 −8 W m −2 sr −1 , and an area of 56 square arc min. The same observation would have taken <2 h with FIFI+LS factoring in the sensitivity gain of at least a factor of 1.4 (to be squared when scaling observing time), the FOV increase by a factor of 1.75 and the use of more efficient observing modes that give a reduction by another factor of 1.5.…”
Section: Science Opportunitiesmentioning
confidence: 76%
See 3 more Smart Citations
“…We can compare FIFI+LS performance improvement to recent observations of FIFI-LS. Indeed, a comparable observation has already been completed with FIFI-LS for NGC6946 in [CII] by Bigiel et al 10 This map was completed in 9.5 h total, providing a signal-to-noise ratio of 4 for a line flux of 1.3 × 10 −8 W m −2 sr −1 , and an area of 56 square arc min. The same observation would have taken <2 h with FIFI+LS factoring in the sensitivity gain of at least a factor of 1.4 (to be squared when scaling observing time), the FOV increase by a factor of 1.75 and the use of more efficient observing modes that give a reduction by another factor of 1.5.…”
Section: Science Opportunitiesmentioning
confidence: 76%
“…of ultra-luminous infrared galaxies and represents an important laboratory, in which to study the origin of the [CII] deficit observed in these galaxies. Bigiel et al 10 presented the results for another full-galaxy [CII] map with FIFI-LS of the nearby spiral galaxy NGC6946. The data allowed disentangling the [CII] luminosities of the arms (73%), center (19%), and interarm regions (8%) of NGC6946.…”
Section: Science With Fifi-lsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another excellent tracer of diffuse gas that is not significantly affected by extinction in the ISM is the [C II] far-infrared (FIR) line at 157.741 μm. Although observed in many galaxies with Herschel (see, e.g., Herrera-Camus et al 2015) and the Stratospheric Observatory for Infrared Astronomy (SOFIA; see, e.g., Pineda et al 2018;Bigiel et al 2020), it has never been used for detailed studies of galaxy bars. The only published study with Herschel data is limited to the circumnuclear region of the barred spiral NGC 1097 (Beirão et al 2012).…”
Section: Introductionmentioning
confidence: 99%